The Effect of Product Quality, Price and Promotion to Customer Satisfaction and Loyalty in You Coffee and Resto in Jagakarsa - Sugiono, Edi; Tia Siti Aisyah (HM Publisher, 2021)
This study was aimed to analyse the effect of product quality, price, promotion on customer satisfaction and the effect of customer loyalty at You Coffee and Resto Jagakarsa, Jakarta, Indonesia. 125 sample were selected by purposive sampling in You Coffee and Resto. Data were collected by questionnaires and Structural Equation Model (SEM) were applies as an analysis technique. The results analysis showed that product quality, price, promotion have positive and significant effect on the customer satisfaction and customer loyalty.product quality, price and promotion need to be increased in order to improve satisfaction and loyalty Customer.